2023
DOI: 10.1136/rmdopen-2022-002864
|View full text |Cite
|
Sign up to set email alerts
|

Association between type I interferon pathway activation and clinical outcomes in rheumatic and musculoskeletal diseases: a systematic literature review informing EULAR points to consider

Abstract: BackgroundType I interferons (IFN-I) contribute to a broad range of rheumatic and musculoskeletal diseases (RMDs). Compelling evidence suggests that the measurement of IFN-I pathway activation may have clinical value. Although several IFN-I pathway assays have been proposed, the exact clinical applications are unclear. We summarise the evidence on the potential clinical utility of assays measuring IFN-I pathway activation.MethodsA systematic literature review was conducted across three databases to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 258 publications
0
11
0
Order By: Relevance
“…SLE patients with an IFN signature could benefit from a human anti-IFN Ab, which competes with IFN-α binding to the receptor IFNAR2, thus preventing the activation of the IFN-α mediated pathways [ 150 ]. Interestingly, a systematic literature review by Rodríguez-Carrio et al [ 151 ] has revealed that measuring type I IFN pathway activation in these patients could potentially help in monitoring the disease activity, the prognosis, and the response to treatment, although assay harmonization and clinical validation are still needed [ 151 ].…”
Section: Pathophysiology Of Systemic Monogenic Autoimmune Disorders A...mentioning
confidence: 99%
“…SLE patients with an IFN signature could benefit from a human anti-IFN Ab, which competes with IFN-α binding to the receptor IFNAR2, thus preventing the activation of the IFN-α mediated pathways [ 150 ]. Interestingly, a systematic literature review by Rodríguez-Carrio et al [ 151 ] has revealed that measuring type I IFN pathway activation in these patients could potentially help in monitoring the disease activity, the prognosis, and the response to treatment, although assay harmonization and clinical validation are still needed [ 151 ].…”
Section: Pathophysiology Of Systemic Monogenic Autoimmune Disorders A...mentioning
confidence: 99%
“…High serum IFN-α is thought to be an hereditable risk factor for SLE, and there are multiple genetic variants in type I IFN pathway genes that are associated with SLE risk 3. Elevated type I IFN signalling, measured using IFN gene signatures (IFNGS), is associated with disease activity, organ involvement and the activity of other immune pathways in patients with SLE 4–7. Transcriptomic analyses have identified additional dysregulated biological pathways in SLE, including B-cell activating factor (BAFF) signalling and modules of genes associated with inflammation and lymphoid signalling 6.…”
Section: Introductionmentioning
confidence: 99%
“…9 Although these cytokines are produced by innate immune cells to activate the immune system and defend against viral and bacterial infections, 9 overexpression of type I IFNs occurs in patients with SLE and other autoimmune diseases, 9 10 and activation of the IFN pathway has been associated with increased SLE disease activity. [11][12][13] Type I IFN-inducible gene expression, measured using the IFN gene signature (IFNGS), provides a method to assess type I IFN pathway activation in individual patients. 14 IFNGS testing in patients with SLE has revealed a bimodal distribution of transcript scores, 15 suggesting that IFNGS-high and IFNGS-low subpopulations may differ with respect to SLE disease characteristics.…”
Section: Introductionmentioning
confidence: 99%